Additions to the fern flora of the Trusmadi Range, Sabah, Malaysia - Mohd Aminur Faiz Suis; Florina Anthony; Maryani Andi Mustapeng Andi; Monica Suleiman (e-VIBS, Faculty of Science and Natural Resources, 2016)
This paper reports the addition of seven species of ferns to the flora of the Trus Madi Range. Leptochilus cf. decurrens Bl. is reported as new to Sabah. These new records are among the 72 species of ferns collected during an ecological study at the northwestern part of Mount Trus Madi in the Tambunan District. With these additions, the number of ferns recorded in the Trus Madi Range stands at 179 species in 76 genera and 23 families.